Cervical artery dissection: fibromuscular dysplasia versus vascular Ehlers–Danlos syndrome. (4th March 2019) - Henrard, Caroline; Belge, Hendrica; Fastré, Sophie; Di Monaco, Silvia; Revencu, Nicole; Hammer, Frank; Pasquet, Agnès; Persu, Alexandre
Abstract: We report the case of a 42-year-old patient referred for suspicion of fibromuscular dysplasia in the context of a carotid artery dissection occurring after a minor trauma. Initial complaints included left hemicrania, lateral diplopia with left 6 th cranial nerve palsy and pulsatile tinnitus. The work-up disclosed a large left carotid-cavernous fistula, as well as more proximal carotid lesions compatible with multifocal fibromuscular dysplasia. Personal history included colonic and uterine perforation. Family history disclosed a fatal hemorrhage due to rupture of a splenic artery aneurysm in the father and an iliac dissection in the sister. Genetic screening revealed a mutation in exon 6 of the COL3A1 gene in the index patient and her sister, confirming the diagnosis of vascular Ehlers–Danlos syndrome (vEDS). This case report shows that images suggestive of fibromuscular dysplasia may be found in patients with demonstrated vEDS. Furthermore, it reminds that in case of cervical artery dissection occurring in a young patient, all efforts should be made to diagnose the underlying condition. In particular, the existence of a family history of arterial dissection, the occurrence of a carotid-cavernous fistula and coexistence with other complications suggestive of a connective tissue disease should prompt physicians to consider the diagnosis of vEDS.